A STRUCTURED WORKSHOP: AN ENDEAVOR TO IMPROVE TEACHERS COMPETENCE IN WRITING SCIENTIFIC JOURNAL ARTICLES - Afrianto Daud; Ando Fahda Aulia; Nita Rimayanti; Mirza Hardian (International Journal of Educational Best Practices, 2020)
The ability to write and publish articles in scientific journals is part of the professional competence of the teacher. The problem is that many teachers have not mastered the skills of writing scientific papers. As a result, many teachers find it difficult to advance in rank, especially for promotion after IV/a. This paper describes a community service activity sponsored by Riau University lecturers which aims to help teachers improve their scientific writing skills. Community Service Activities were performed at a SMAIT (Islamic Integrated High School) in Pekanbaru, Riau. This paper further explains the concept of the workshop, the content of the workshop materials, and the effectiveness of the workshop. This workshop lasted for two months with three face-to-face training sessions. The rest was done online via the Google Classroom platform. The material content covers the basic principles of scientific writing, the steps for writing scientific journals, how to cite and make references, including how to automatically quote from reference manager applications such as Mendeley, and how to submit articles through the Online Journal System (OJS). Data from the survey conducted at the end of the community service activity showed that, in general, this activity was well and effectively carried out. The majority of participants (72.7%) stated that their motivation to write increased after attending the training. Their knowledge of writing scientific articles have improved after training. Their ability in writing scientific journals is also relatively better than before following this structured workshop.